MANAGEMENT OF CHRONIC OTITIS EXTERNA, RHINITIS, AND CONJUNCTIVITIS CAUSED BY PSEUDOMONAS SP., BACILLUS SP., AND CANDIDA SP. INFECTION IN A PERSIAN CAT - Ndoy, Maria Ursulin Tasya; Soma, I Gede; Jayanti, Putu Devi (Buletin Veteriner Udayana, 2026)
Chronic otitis externa is an inflammatory condition that can involve multiple pathogens such as bacteria and fungi, and may be associated with disorders of adjacent sensory systems, including the nose and eyes. This case report aims to describe the management of a case of chronic otitis externa accompanied by rhinitis and conjunctivitis in a six-year-old female Persian cat. Diagnostic methods include history taking, complete physical examination, and supporting examinations such as hematology, otoscopy, rapid testing for feline calicivirus and feline herpesvirus-1, as well as bacterial and fungal isolation and identification from ear, nasal, and ocular exudates. Results revealed infection involving Pseudomonas sp., Bacillus sp., and Candida sp. in the ears, and Staphylococcus sp. in the nose and eyes. Otitis therapy involved ear cleaning using Ilium Oticlean® and topical application of a combination of gentamicin, nystatin, and fluocinolone acetonide (Topigen®) administered at three drops q12h for 14 days. Rhinitis and conjunctivitis therapy included systemic antibiotic amoxicillin-clavulanic acid (ClaPet 250®) at 20 mg/kg BW q12h for 7 days, and anti-inflammatory methylprednisolone at 1 mg/kg BW q24h for 3 days. A positive therapeutic response for rhinitis was observed after 7 days of treatment, whereas conjunctivitis showed slower improvement and required additional therapy with Erlamycetin Plus® ophthalmic ointment 3.5 g, applied once q12h for 5 days. Treatment of chronic otitis externa showed significant improvement after 14 days. Therefore, management of otitis externa, rhinitis, and conjunctivitis requires a multimodal approach and comprehensive diagnosis to confirm the etiology and support appropriate therapy. Special attention to environmental hygiene and care practices is essential to prevent recurrence.